Effect of high hydrostatic pressure on Salmonella enterica subsp. enterica in Nutrient Broth and dried parsley. (1st February 2022) - Dittrich, Anna Joana; Ludewig, Martina; Rodewald, Steffen; Braun, Peggy Gabriele; Wiacek, Claudia
Abstract: The effect of high hydrostatic pressure on Salmonella isolates in Nutrient Broth (10 3, 10 8  CFU mL −1 ) and dried parsley (10 3, 10 7  CFU g −1 ) was determined at 250–550 MPa for 2.5–10.0 min at 25 °C. Reduction efficiency as well as quality parameters (total chlorophyll, phenolic compounds, spectrophotometric colour) of parsley were investigated. At selected parameters (2.5, 5.0 min; 550 MPa) sensory analysis was performed and the impact of prolonging Salmonella inoculation time before treatment (48 h) and post-treatment storage (70 days) was examined. Reductions of 0.9–8.8 log CFU were achieved in Nutrient Broth, with higher pressures or longer dwell times required to completely reduce viable cells at 10 8  CFU mL −1 . In parsley, reductions were significantly lower (p < 0.05), ranging between 1.2 and 2.5 log CFU at 10 3  CFU g −1 . The reduction efficiency was further decreased by increasing the contamination level (10 7  CFU g −1 : 0.7–1.5 log CFU) or extension of the inoculation time (10 3  CFU g −1 : 1.1–1.3 log CFU). Total chlorophyll was not significantly influenced, while phenolic compounds slightly increased (3.5–8.3%). Sensory analysis proved significant but no adverse differences in colour and odour of pressure-treated parsley. Highlights: Significant reductions of Salmonella are shown in both matrices using HHP. The effect depends on the matrix, contamination level and inoculation time before HHP. Treatment affects the yield of phenolic compounds, while total chlorophyll is stable. Sensory analysis reveals significant but no adverse differences in colour and odour. HHP at 550 MPa for 2.5 or 5.0 min is identified as most suitable.